2006
DOI: 10.1172/jci27933
|View full text |Cite
|
Sign up to set email alerts
|

The A2B adenosine receptor protects against inflammation and excessive vascular adhesion

Abstract: Adenosine has been described as playing a role in the control of inflammation, but it has not been certain which of its receptors mediate this effect. Here, we generated an A 2B adenosine receptor-knockout/reporter gene-knock-in (A 2B AR-knockout/reporter gene-knock-in) mouse model and showed receptor gene expression in the vasculature and macrophages, the ablation of which causes low-grade inflammation compared with age-, sex-, and strain-matched control mice. Augmentation of proinflammatory cytokines, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
411
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(458 citation statements)
references
References 59 publications
40
411
7
Order By: Relevance
“…In addition, the antiinflammatory effects of A 2B have already been described in literature. Yang and colleagues reported that A 2B null mice present augmentation of pro-inflammatory cytokine levels, such as TNF-α, upregulation of vascular adhesion proteins, and leukocyte migration in response to lipopolysaccharide (LPS)-induced acute inflammation [50]. Thus, our study provides the first evidence that adenosine and inosine can activate adenosine A 2A and A 2B receptors in acute pleural inflammation, and therefore, being important regulators of this process.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, the antiinflammatory effects of A 2B have already been described in literature. Yang and colleagues reported that A 2B null mice present augmentation of pro-inflammatory cytokine levels, such as TNF-α, upregulation of vascular adhesion proteins, and leukocyte migration in response to lipopolysaccharide (LPS)-induced acute inflammation [50]. Thus, our study provides the first evidence that adenosine and inosine can activate adenosine A 2A and A 2B receptors in acute pleural inflammation, and therefore, being important regulators of this process.…”
Section: Discussionsupporting
confidence: 55%
“…To examine whether the low-affinity A2bARs have an effect on vascular phenotypes, we generated an A2bAR KO/reporter gene knockin mouse model (10). Our earlier studies demonstrated that the A2bARs are notably expressed in vascular cells and macrophages and protect against excessive vascular adhesion (10), suggesting that A2bARs mediate a protective effect on the vasculature.…”
Section: Inflammation ͉ Cxcr4mentioning
confidence: 99%
“…For these reasons caffeine is generally believed to act on A 1 R and A 2A R to exert most of its effects, at least when given in lower doses (18). However, a recent study showed that A 2B R knockout (A 2B RKO) mice have elevated cytokines, vascular adhesion molecules, and leukocyte adherence (49), indicating that A 2B R is probably also activated by endogenous adenosine. This could indicate that at some sites local adenosine concentrations may be high enough to activate A 2B R.…”
mentioning
confidence: 99%